2021
DOI: 10.1038/s41598-021-01285-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bathing in neutral bicarbonate ion water

Abstract: Percutaneously absorbed carbon dioxide enhances blood flow. The mechanism by which it does so is unclear, but we hypothesized that it involves bicarbonate ions. BALB/c mice were bathed in neutral bicarbonate ionized water (NBIW) and showed increased blood bicarbonate levels and blood flow via phosphorylation of peripheral vascular endothelial nitric oxide synthase (eNOS) and production of nitric oxide (NO). Phosphorylation of eNOS and NO production were also increased in human umbilical vein endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…(40,41) Therefore, increased NO production and eNOS phosphorylation indicate vasodilation and blood flow enhancement. (42) Our experiment on HUVECs found increased phosphorylation levels of eNOS and increased NO production in the presence of NCS polyphenols, especially saponarin and isoschaftoside. The in vivo experiments showed that saponarin and isoschaftoside increased blood flow in the submandibular region of the mice.…”
Section: Discussionmentioning
confidence: 59%
“…(40,41) Therefore, increased NO production and eNOS phosphorylation indicate vasodilation and blood flow enhancement. (42) Our experiment on HUVECs found increased phosphorylation levels of eNOS and increased NO production in the presence of NCS polyphenols, especially saponarin and isoschaftoside. The in vivo experiments showed that saponarin and isoschaftoside increased blood flow in the submandibular region of the mice.…”
Section: Discussionmentioning
confidence: 59%
“…11 Previously, we performed experiments with neutral bicarbonate ionized water (NBIW) and showed that bathing in NBIW tends to increase blood bicarbonate ion concentrations and increase blood ow by increasing expression and phosphorylation levels of endothelial nitric oxide synthase and levels of nitric oxide (NO) in femoral vascular tissue, effects that are associated with enhanced blood ow. 12 Moreover, in a preliminary randomized controlled trial conducted on the basis of those experiments, we found that the effects of higher body temperature upon waking and one hour after bathing tended to occur earlier in the intervention than in the control group and that vigor/activity improved in the mood states pro le. 12 Therefore, we conducted a randomized, open-label, crossover trial to study the effect of NBIW on sleep, mental stress, and immune function.…”
Section: Introductionmentioning
confidence: 81%
“…12 Moreover, in a preliminary randomized controlled trial conducted on the basis of those experiments, we found that the effects of higher body temperature upon waking and one hour after bathing tended to occur earlier in the intervention than in the control group and that vigor/activity improved in the mood states pro le. 12 Therefore, we conducted a randomized, open-label, crossover trial to study the effect of NBIW on sleep, mental stress, and immune function. In particular, to more accurately evaluate the e cacy of NBIW in improving mental stress, we assessed sleep quality, which correlates with stress, not only subjectively with a questionnaire-based analysis, but also objectively with an activity meter.…”
Section: Introductionmentioning
confidence: 81%
“…AS care contains carbonate, sodium dichloroisocyanurate, and sodium dichloroisocyanurate hydrolyzes to produce hypochlorous acid (HOCl) simultaneously with carbon dioxide generation. Transdermally absorbed carbon dioxide is converted to bicarbonate ions, which act directly on endothelial cells to increase nitric oxide (NO) production through phosphorylation of endothelial nitric oxide synthase (eNOS), a process that is considered to improve blood flow [ 5 ]. Hypochlorous acid (HOCl) has both antimicrobial and deodorizing effects on wounds [ 6 ].…”
Section: Discussionmentioning
confidence: 99%